2022
DOI: 10.3389/fgene.2022.994208
|View full text |Cite
|
Sign up to set email alerts
|

A newly defined basement membrane-related gene signature for the prognosis of clear-cell renal cell carcinoma

Abstract: Background: Basement membranes (BMs) are associated with cell polarity, differentiation, migration, and survival. Previous studies have shown that BMs play a key role in the progression of cancer, and thus could serve as potential targets for inhibiting the development of cancer. However, the association between basement membrane-related genes (BMRGs) and clear cell renal cell carcinoma (ccRCC) remains unclear. To address that gap, we constructed a novel risk signature utilizing BMRGs to explore the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…LOXL2 is overexpressed in RCC, and its silencing suppresses the migration and invasion of cancer cells in ccRCC cell lines [ 39 ]. FREM1 has been identified as an independent prognostic factor in ccRCC and is negatively correlated with tumor staging [ 40 , 41 ]. Although MUC16 exhibits a high mutation frequency in ccRCC, studies on its prognostic implications are limited [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…LOXL2 is overexpressed in RCC, and its silencing suppresses the migration and invasion of cancer cells in ccRCC cell lines [ 39 ]. FREM1 has been identified as an independent prognostic factor in ccRCC and is negatively correlated with tumor staging [ 40 , 41 ]. Although MUC16 exhibits a high mutation frequency in ccRCC, studies on its prognostic implications are limited [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have already attempted to mine public databases to identify prognostic gene signatures related to BM proteins in tumors. For example, Cai et al identified a 7-gene signature associated with basement membrane proteins that predicted the prognostic status of breast cancer patients and provided insights for immunotherapy ( Cai et al, 2022 ); Zhou et al developed a risk model using 8 BMRGs, which revealed that clear-cell renal cell carcinoma patients in the low-risk group had a better response to immunotherapy ( Zhou et al, 2022 ); Lin et al established a 7-BMRG signature and identified five small compounds that could potentially be used for the treatment of pancreatic cancer patients, providing new perspectives for a deeper understanding of this disease ( Lin et al, 2023 ). Overall, these studies highlight the significance of basement membrane proteins in the precise treatment of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly associated with several immune cells in ccRCC, such as activated dendritic cell, central memory CD8 T cell, central memory CD4 T cell, and activated CD4 T cell. 61 Finally, the gene EPHA3, Eph receptor tyrosine kinases, formerly known as HEK, contribute to tumor development, modulating cell-cell adhesion and survival during invasion, neo-angiogenesis and metastasis. 62 Therefore, the gene EPHA3 represents a potential source of tumorspecific antigens recognized on tumor cells that express human leukocyte antigens (HLA) class II molecules.…”
Section: Open Accessmentioning
confidence: 99%